PENGEMBANGAN PERANGKAT LUNAK REMOTE PROCESS UNTUK PENGENDALIAN KOMPUTER JARAK JAUH - Bersama Sinuraya (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2017)
With the development of telecommunication techniques and data processing systems that are closely related to communication between computer users with one another computer. This rapidly growing computer and telecommunication network technology provides a means and convenience for programmers to design an application that communicates data between client computers and server computers. Active-X provided by the computer's operating system also supports all the processes described above. With the support of all these aspects can be designed an application that can control a process on a PC from different places. Thus theresults of this remote program implementation is expected to be useful to streamline user performance in managing the computer system administrator